Effect of oral dosage of Spirulina platensis and silver nanoparticles on glucose, lipid profile, and liver enzymes in male rats induced di-abetics by alloxan - Oleiwi, Saad D. (Journal of Kerbala for Agricultural Sciences, 2024)
Diabetes is believed to be one of the most important challenges that are facing societies around the world. The research was conducted to determine the effectiveness of 150 mg/ml of Spirulina platensis and 10 mg/ml of silver nanoparticles Ag-NPs on the sugar level, lipid profile, and liver enzyme concentration in male rats. Diabetes was induced with alloxan and bred for four weeks. The rats were divided randomly into five groups and every single group contained five rats; M1 was the control group, M2 was a treated diabetic rat, M3 treated diabetic rats with 10 mg/ml Ag-NPs, M4 treated diabetic rats with 150 mg/ml S. platensis and M5 group with diabetic rats that were treated with 10 mg/ml Ag-NPs + 150 mg/ml S. platensis. The results showed that the group of rats infected with Alloxan (M2) caused negative effects at a significant level (P<0.05) on the blood sugar level, while the group of rats treated with Ag-NPs (M3) or S. platensis (M4) or both (M5) showed a positive effect on the blood glucose rate, which reached 292.6, 210.5, and 199.3 mg/dl, respectively, compared to the (M2) group, which was 441.8 mg/dl. The results of the lipids profile, the group with diabetes (M2) showed an increase in the level of triglycerides (TG), cholesterol (TC), low-density lipoproteins (LDL), and very low-density lipoproteins (VLDL), and a decrease in the level of high-density lipoproteins (HDL). The treatment groups M3, M4, and M5 improved significantly positive blood lipid levels. The same situation applied to the liver enzymes AST, ALT, and ALP, whose values decreased significantly in the treatment groups (M3, M4, and M5) compared to the infection group (M2).